Strategi Dinas Koperasi, Usaha Mikro, Perindustrian dan Perdagangan dalam Mengembangkan Usaha Mikro Berbasis Potensi Kelautan dan Perikanan di Kabupaten Bintan - Lili Pranola; Fitri Kurnianingsih; Ramadhani Setiawan (Lembaga Pengembangan Kinerja Dosen, 2023)
Bintan Regency has abundant marine and fishery potential because most of it’s territory is the ocean. Micro enterprises with the type of marine fisheries are in third place after culinary and retail in this district. However, there are still some problems in developing marine and fisheries potential based micro enterprises in Binan Regency, including the lack of digital marketing implementation for micro business actors. This study aims to find out how DKUPP is strategy is in developing marine and fisheries potential based micro enterprises in Bintan Regency. This study used a qualitative approach with a descriptive research type. Data collection techniques used were observation, interviews, and documentation. Research results (1) On the indicators of creating a good business climate, DKUPP Bintan Regency has implemented several practices or programs in order to develop micro enterprises, especially those based on marine and fisheries potential in Bintan Regency. (2) In producing integrated information, DKUPP Bintan Regency disseminated all information to micro enterpreneurs in Bintan Regency through Whatsapp Gropus, Instagram social media, radio broadcast and writing to the sub district. (3) In the establishment of a consultation center, DKUPP Bintan Regency has and Integrated Business Service Center (PLUT) but can’t run optimally because human resources are still inadequate and the PLUT building is still far from the reach of micro enterpreneurs in Bintan Regency. (4) In creating a join marketing system, DKUPP Bintan Regency has carried out several methods, including by holding bazaars, promoting micro business products via Whatsapp and implementing a new policy plans related to e-catalogue and reinforcement. (5) On the indicators of creating research and development institutions, Bintan Regency does not yet have a research center specifically designated for business actors in Bintan Regency. The conclusion of the research is that the strategy implemented by DKUPP Bintan Regency has not run optimally because there are still several obstacles in the development process.